Preserving Wayang Golek: The Rationale of Radio Komunitas Seni dan Budaya Maja FM Program Selection - Anwar, Rully Khairul; Besthari, Bian; Damayani, Ninis Agustini; Khadijah, Ute Lies Siti (Jurnal Kajian Jurnalisme, 2024)
Wayang Golek as an integral part of the Sundanese culture, is at risk due to globalization and modern influences. To counter this, RKSB Maja FM, a community radio in Bandung, West Java, has initiated the "Preserving the Art of Wayang Golek" program as a form of local cultural preservation. This research aims to understand the process and motivation behind the selection of Wayang Golek art performances for broadcast on RKSB Maja FM, as well as to explore its impact on the preservation of Sundanese culture and its influence on the listening community. This study uses a qualitative method with an instrumental case study approach. It gathers information through in-depth interviews with RKSB Maja FM members involved in the selection and implementation of the program, as well as the analysis of related documents. It gathers information through in-depth interviews with RKSB Maja FM members involved in the selection and implementation of the program, as well as the analysis of related documents. The research findings indicate that RKSB Maja FM chose the program "Preserving the Art of Wayang Golek" because Wayang Golek is a distinctive identity of Sundanese society and holds significant cultural values. The program aims to protect the continuity of this art form from outside influences and to ensure that the younger generation does not forget about Wayang Golek. RKSB Maja FM sees radio broadcasting as an effective medium for preserving and introducing Wayang Golek to the broader community. In conclusion, the broadcasting program "Preserving the Art of Wayang Golek" is RKSB Maja FM's effort to safeguard the cultural heritage of Sundanese culture and strengthen the local cultural identity amidst the challenges of globalization.